PENGEMBANGAN PERANGKAT RENCANA PEMBELAJARAN SEMESTER (RPS) BERBASIS KECERDASAN INTERPERSONAL UNTUK MENGEMBANGKAN KOMPETENSI SOSIAL MAHASISWA - Nurfadilah Mahmud; Rezki Amaliyah AR; Nursafitri Amin; Muhammad Jufri; Alimuddin Alimuddin (PEDAMATH: Journal on Pedagogical Mathematics, 2018)
This research is a development research referred to Four-D model. This research aims to develop Interpersonal Intelligence-based of basic statistics learning devices to improve students’ social competence. This type of Four-D model development research consists of four stages: (1) define, (2) design, (3) develop, and (4) disseminate. The learning devices produced are RPS that meet valid criteria.